A Survey on Assistive Systems - Indhumathi, R; Geetha, A (International Journal of Computer Sciences and Engineering, 2025)
Assistive technology is any hardware or software designed to enable independence for disabled and older people. Technologies are growing up day to day. The disabled and older people are very difficult to adopt new technologies. Disabled people are an important part of our society who has not yet received the same opportunities as others in their inclusion in the Information society. It is necessary to develop easily accessible systems for computers to achieve their inclusion within the new technologies. The main objective of this paper is to review and discuss the assistive systems that help disabled and older people to be drawn nearer to new technologies